1998
DOI: 10.1152/ajpheart.1998.275.5.h1585
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite is a contractile agonist of cerebral artery smooth muscle cells

Abstract: On reperfusion of ischemic tissue, a prolonged phase of vasoconstriction occurs, the mechanism of which is poorly understood. However, it is known that peroxynitrite (ONOO−) is formed during reperfusion. In this study the contractile properties of ONOO− were investigated in Wistar rat middle cerebral arteries. The effects of ONOO− on vessel diameter were dose dependent. Low-dose ONOO− (10 μM) caused vessels to constrict by 15%. At an intermediate concentration of 25 μM, the effect of ONOO−was variable, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 14 publications
5
49
3
Order By: Relevance
“…These data were in agreement with studies in other arterial ring preparations from different animals [23,125,144], and are in agreement with the concept that the endothelium has no significant role in the modulation of PN responses [23]. However, these findings are in contrast to observations in a cerebral smooth muscle cell preparation and in middle cerebral arteries of the rat where PN induced contraction [195,196]. In this study, the PN-induced relaxation was reproducible without the development of tachyphylaxis, suggesting that the action of PN is reversible and does not cause vascular damage.…”
Section: Vasorelaxant Properties Of Peroxyni-tritesupporting
confidence: 92%
“…These data were in agreement with studies in other arterial ring preparations from different animals [23,125,144], and are in agreement with the concept that the endothelium has no significant role in the modulation of PN responses [23]. However, these findings are in contrast to observations in a cerebral smooth muscle cell preparation and in middle cerebral arteries of the rat where PN induced contraction [195,196]. In this study, the PN-induced relaxation was reproducible without the development of tachyphylaxis, suggesting that the action of PN is reversible and does not cause vascular damage.…”
Section: Vasorelaxant Properties Of Peroxyni-tritesupporting
confidence: 92%
“…35 In addition, studies on cell cultures suggest that homocysteine may also promote increased generation of ROS 18 -21 by downregulating antioxidant mechanisms, such 37 We found that ONOO Ϫ is a potent vasoactive agent that elicits substantial TxA 2 -mediated constriction in skeletal muscle arterioles ( Figure 4A), similar to its action in cerebral arteries. 34 Direct measurements of ONOO Ϫ metabolism have shown that ONOO Ϫ (formed from xanthine-oxidase-derived superoxide and NO) can be effectively scavenged by urate in biological systems. 31 The finding that urate prevented ONOO Ϫ -induced arteriolar constrictions ( Figure 4A) confirms that urate acts as a potent ONOO Ϫ scavenger under the present experimental conditions as well.…”
Section: Discussionmentioning
confidence: 99%
“…Immediately before each experiment, an aliquot of the stock solution was diluted into an ice-cold alkaline solution, 34 from which an appropriate volume was administered immediately in the organ bath. SQ 29,548 (Cayman Chemicals) was dissolved in ethanol; urate (Calbiochem) was dissolved in alkaline buffer.…”
Section: Methodsmentioning
confidence: 99%
“…-ATPase type-2 [11,[38][39][40][41]. In addition, peroxynitrite has been shown to induce degranulation of eosinophils, epithelial damage and AHR [33,34], as well as airway microvascular hyperpermeability [35] in guinea pigs.…”
Section: +mentioning
confidence: 99%